Mexico's External Debt and the Return to Voluntary Capital Market Financing - El-Erian, Mohamed (IMF Working Papers; Working Paper ;, 1991)
The paper analyzes the evolution of Mexico's approach to commercial bank debt restructuring since the outbreak of the 1982 debt servicing problems. It discusses the key elements of the approach, their implementation, and their interaction with developments in the 'international debt strategy.' It focusses, in particular, on factors contributing to the emergence of comprehensive market-based debt and debt service reduction operations. Together with the sustained implementation of appropriate economic policies, these operations have contributed to Mexico's return to voluntary international capital market financing. The paper discusses the major aspects of this market re-entry process.